2014
DOI: 10.1371/journal.pone.0103249
|View full text |Cite
|
Sign up to set email alerts
|

MDSCs Mediate Angiogenesis and Predispose Canine Mammary Tumor Cells for Metastasis via IL-28/IL-28RA (IFN-λ) Signaling

Abstract: BackgroundMyeloid-derived suppressor cells (MDSCs) function in immunosuppression and tumor development by induction of angiogenesis in a STAT3-dependent manner. Knowledge of MDSC biology is mainly limited to mice studies, and more clinical investigations using spontaneous tumor models are required. Here we performed in vitro experiments and clinical data analysis obtained from canine patients.MethodsUsing microarrays we examined changes in gene expression in canine mammary cancer cells due to their co-culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 36 publications
2
39
0
6
Order By: Relevance
“…Changes in gene expression in mammary cancer cell lines after co-culturing with myeloid-derived suppressor cells (MDSC) were recently investigated. 56 Microarray analysis gene expression revealed that 107 genes were significantly upregulated in cell lines after MDSC treatment, most of them being involved in inflammation, interleukin signalling pathway, and cytoskeletal regulation. The study then focused on the IL-28/IL-28R pathway by knocking down IL-28R, and demonstrated that treatment with IL-28 promotes angiogenesis, epithelial-mesenchymal transition, and enhances mammary tumour invasion and migration.…”
Section: Cancer Progression and Development Of Metastatic Clonesmentioning
confidence: 99%
“…Changes in gene expression in mammary cancer cell lines after co-culturing with myeloid-derived suppressor cells (MDSC) were recently investigated. 56 Microarray analysis gene expression revealed that 107 genes were significantly upregulated in cell lines after MDSC treatment, most of them being involved in inflammation, interleukin signalling pathway, and cytoskeletal regulation. The study then focused on the IL-28/IL-28R pathway by knocking down IL-28R, and demonstrated that treatment with IL-28 promotes angiogenesis, epithelial-mesenchymal transition, and enhances mammary tumour invasion and migration.…”
Section: Cancer Progression and Development Of Metastatic Clonesmentioning
confidence: 99%
“…(5) zauważyli, że u kobiet z zaawansowanym rakiem piersi stosunek ten był wyższy niż u kobiet zdrowych. Takie samo zjawisko wykazano u suk z przerzutującymi nowotworami gruczołu sutkowego (29). W ograniczaniu odpowiedzi przeciwnowotworowej cytotoksycznych limfocytów T biorą również udział limfocyty T regulatorowe i mieloidalne komórki supresorowe.…”
Section: Artykuł Przeglądowy Reviewunclassified
“…: nasieniaku (14,48), czerniaku (36,45), raku okrężnicy (12,32), raku szyjki macicy (35), raku jajnika (46,52), raku nabłonka pęcherza moczowego (40) i raku żołądka (22). Nasze badania wykazały wzrost liczby limfocytów Treg u psów w zaawansowanym stadium rozwoju raka sutka zarówno we krwi obwodowej, jak i na terenie guza nowotworowego (29,30).…”
Section: Artykuł Przeglądowy Reviewunclassified
See 2 more Smart Citations